Sistem Absensi Otomatis menggunakan Radio Frequency Identification berbasis Mikrokontroler ESP32 - Kahar, Saipul; Thamrin, Thamrin (Lembaga Yasin AlSys, 2025)
This study stems from the need to improve the efficiency of student attendance recording in schools, which is still predominantly carried out manually and remains ineffective. The primary objective of the research is to develop an automated attendance system based on the ESP32 microcontroller, integrated with Radio Frequency Identification (RFID) technology and the Internet of Things (IoT) concept. The method employed is Rapid Application Development (RAD), which supports fast and iterative system design and testing. The system is built using key components such as the MFRC522 RFID reader, 16x2 LCD display, real-time clock (RTC), 4x4 keypad, buzzer, and I2C communication module, all integrated into a single automated attendance device. The software was developed using Arduino IDE for microcontroller programming and Visual Studio Code for the web interface, while the database was constructed using MySQL via XAMPP. Testing results indicate that all modules function optimally; the system accurately reads RFID UIDs, displays real-time attendance data on the LCD, and automatically stores information in the database. In conclusion, the system effectively replaces manual attendance methods and demonstrates high potential for broad implementation in educational institutions.